2015
DOI: 10.1371/journal.pone.0124765
|View full text |Cite
|
Sign up to set email alerts
|

The GLP-1 Receptor Agonist Exendin-4 and Diazepam Differentially Regulate GABAA Receptor-Mediated Tonic Currents in Rat Hippocampal CA3 Pyramidal Neurons

Abstract: Glucagon-like peptide-1 (GLP-1) is a metabolic hormone that is secreted in a glucose-dependent manner and enhances insulin secretion. GLP-1 receptors are also found in the brain where their signalling affects neuronal activity. We have previously shown that the GLP-1 receptor agonists, GLP-1 and exendin-4 enhanced GABA-activated synaptic and tonic currents in rat hippocampal CA3 pyramidal neurons. The hippocampus is the centre for memory and learning and is important for cognition. Here we examined if exendin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Consequently, LDTg GABA neurons may potentially be the target of GLP-1RA exendin-4's pharmacological action in cocaine (Hernandez et al, 2020). Consistent with these results, the patch-clamp recordings found that GLP-1 and exendin-4 temporarily regulated synaptic and tonic currents activated by GABA in CA3 pyramidal neurons, and thereby augmenting GABA signaling in CA3 Pyramidal Neurons (Jin et al, 2015;Babateen et al, 2017;Korol et al, 2015). Overall, the translational implications of these findings indicate an essential yet largely unexplored effects of GLP-1RAs on LDTg GABA neurons and a novel neurobiological mechanism by which GLP-1RAs attenuate cocaine-seeking and reinstatement.…”
Section: Glutamate Mechanismsupporting
confidence: 69%
“…Consequently, LDTg GABA neurons may potentially be the target of GLP-1RA exendin-4's pharmacological action in cocaine (Hernandez et al, 2020). Consistent with these results, the patch-clamp recordings found that GLP-1 and exendin-4 temporarily regulated synaptic and tonic currents activated by GABA in CA3 pyramidal neurons, and thereby augmenting GABA signaling in CA3 Pyramidal Neurons (Jin et al, 2015;Babateen et al, 2017;Korol et al, 2015). Overall, the translational implications of these findings indicate an essential yet largely unexplored effects of GLP-1RAs on LDTg GABA neurons and a novel neurobiological mechanism by which GLP-1RAs attenuate cocaine-seeking and reinstatement.…”
Section: Glutamate Mechanismsupporting
confidence: 69%
“…Similarly, GABA A receptor-mediated spontaneous inhibitory postsynaptic current in hippocampal CA3 pyramidal neurons are increased by GLP-1 and exendin-4 in an exendin 3 (9-39)-and TTX-sensitive manner [44,45]. Again, these results indicate that GLP-1R activation can evoke GABA release from presynaptic elements.…”
Section: Figmentioning
confidence: 71%
“…GLP-1, an incretin, is not only secreted from intestinal L cells, but also is expressed in neurons of the central nervous system 43 . Many studies have revealed that GLP-1 32 , 44 , EX-4 45 - 47 , and other agonists of GLP-1R 40 , 48 have a neuroprotective role against neurodegenerative cell death, traumatic brain injury, and ischemic stroke. Previous reports indicate that the neuroprotective effects of GLP-1 and EX-4 involve reducing infarct size and stoke volume 28 , 32 as well as anti-apoptotic effects 28 , 39 .…”
Section: Discussionmentioning
confidence: 99%